KARAKTERISASI PRAKTIKUM BIOKIMIA BERBASIS KONTEKS LOKAL BENGKULU - Amida, Nadia; Florentina Maria Titin Supriyanti (ALOTROP, 2025)
This study aims to identify the characteristics of a biochemistry practicum program on DNA isolation from local Bengkulu citrus, developed to enhance students’ systems thinking skills. A descriptive analysis was conducted through the review of course outlines, practicum implementation documents, student learning modules, and worksheets, as well as observations of practicum sessions and evaluations of students’ learning experiences. The practicum program was implemented with 37 students enrolled in a Biochemistry course at a public university in Bandung. The findings reveal three key characteristics. First, the practicum was restructured from a textbook-based model into a contextual practicum using local Bengkulu citrus as an authentic sample. Second, the practicum employed modern laboratory tools—including microtubes, micropipettes, vortex mixers, and centrifuges—which improved the accuracy of DNA isolation and visualization. Third, the activity design integrated systems thinking skills through component analysis, process interrelationships, and result interpretation. Overall, the developed practicum is contextual, modern, and systems-oriented, enhancing both the relevance and quality of students’ laboratory learning experiences